Pengujian Fraud Diamond Theory Pada Indikasi Financial Statement Fraud Di Indonesia - Suparmini, Ni Kadek; Ariyanto, Dodik; Andika Pradnyana Wistawan, I Made (E-Jurnal Akuntansi, 2020)
This study aims to obtain empirical evidence of fraud diamond theory. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2015-2017 period. The sample determination method used is nonprobability sampling with purposive sampling technique. There are 145 companies as a population with a total of 66 companies as samples. The data analysis technique used is multiple linear regression. Based on the results of the analysis, it was stated that the nature of industry had a negative effect on indications of financial statement fraud while financial need, auditor firm size, and change of directors had no effect on indications of financial statement fraud. This study has implications for shareholders, regulators, or parties who use information in financial statements as a consideration in providing an assessment of the chances of fraudulent actions on the company's financial statements . Keywords: Diamond Fraud; Financial Statement Fraud.